2022
DOI: 10.3390/ijms23073840
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Gene Expression Profile Response to Drought Stress in Populus ussuriensis Using PacBio SMRT and Illumina Sequencing

Abstract: In this study, we characterized the gene expression profile in the roots of Populus ussuriensis at 0, 6, 12, 24, 48 and 120 h after the start of polyethylene glycol (PEG)-induced drought stress using PacBio single-molecule real-time sequencing (SMRT-seq) and Illumina RNA sequencing. Compared to the control, 2244 differentially expressed genes (DEGs) were identified, and many of these DEGs were associated with the signal transduction, antioxidant system, ion accumulation and drought-inducing proteins. Changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 82 publications
1
10
0
Order By: Relevance
“…The amino acid (AA) content was measured using an AA assay kit. The superoxide dismutase (SOD) activity was measured using a total SOD assay kit ( Li et al., 2022 ). The peroxidase (POD) activity was measured using a POD assay kit ( Li et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The amino acid (AA) content was measured using an AA assay kit. The superoxide dismutase (SOD) activity was measured using a total SOD assay kit ( Li et al., 2022 ). The peroxidase (POD) activity was measured using a POD assay kit ( Li et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The superoxide dismutase (SOD) activity was measured using a total SOD assay kit ( Li et al., 2022 ). The peroxidase (POD) activity was measured using a POD assay kit ( Li et al., 2022 ). The malondialdehyde (MDA) content was measured using a MDA assay kit ( Li et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DE analysis is widely used to analyze the forest plant responses to biotic and abiotic stresses, including drought, heat, salinity, flooding, cold, ultraviolet radiation, diseases, and insects [94,95]. For instance, the gene expression analysis in poplar root under polyethylene glycol-induced drought stress by TGS and NGS transcriptomic sequencing revealed several differentially expressed genes related to plant responses to drought in the biosynthesis and metabolism pathways [96]. In addition, the dual RNA-seq analysis of the interactions between Norway spruce and Heterobasidion revealed that several genes involved in the abscisic acid signaling were differentially expressed in Norway spruce, which might contribute to the Norway spruce response to the pathogen attack [97].…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Finally, phenylpropanoid metabolism was observed in the pathway enrichment analysis, and this pathway is one of the most important metabolisms in plants, contributing to plant development and plant-environment interactions (Dong and Lin 2021). Studies have revealed that drought, salt stress and biotic stresses induce lignin deposition through regulating phenylpropanoid metabolism to enhance stress tolerance in H. ammodendron(Nakabayashi and Saito 2015;Li et al 2022). The litter of H. ammodendron is degraded by microorganisms in UC soil, and phenylpropanoid metabolism compounds are dissolved in the soil, where they can gradually form a concentration gradient.…”
mentioning
confidence: 99%